2016
DOI: 10.5483/bmbrep.2016.49.8.090
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Neuregulin-2 as a novel stress granule component

Abstract: Stress Granules (SGs) are microscopically visible, phase dense aggregates of translationally stalled messenger ribonucleoprotein (mRNP) complexes formed in response to distinct stress conditions. It is generally considered that SG formation is induced to protect cells from conditions of stress. The precise constituents of SGs and the mechanism through which SGs are dynamically regulated in response to stress are not completely understood. Hence, it is important to identify proteins which regulate SG assembly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Interestingly, there appears to be a network between TUBB1, ASB4, and PDE5A, suggesting that Class I represents a subpopulation defined by regulation of vasculogenesis (Figure 2) [33][34][35]. plasticity [37,38]. ZNF3 is a zinc-finger protein that is differentially expressed in AD and is involved in cell differentiation and proliferation [39].…”
Section: / 29mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there appears to be a network between TUBB1, ASB4, and PDE5A, suggesting that Class I represents a subpopulation defined by regulation of vasculogenesis (Figure 2) [33][34][35]. plasticity [37,38]. ZNF3 is a zinc-finger protein that is differentially expressed in AD and is involved in cell differentiation and proliferation [39].…”
Section: / 29mentioning
confidence: 99%
“…by NRG2 and ZNF3. Neuregulins (NRGs) are a member of epidermal growth factor (EGF)-related proteins, which stimulate ErbB-receptor tyrosine phosphorylation that elicits different downstream signaling pathways such as MAPK, PI3, PKC, and JAK-STAT pathways and are associated with synaptic plasticity [37,38]. Neuregulin-2 (Nrg2) dysregulation has been associated with cancer, schizophrenia, and AD [37].…”
Section: / 29mentioning
confidence: 99%
“…Even genes and proteins which are associated with bipolar disorder converge on UPR-related pathways controlling translation initiation and RNA processing (Carter, 2007; Darby et al, 2016; Laguesse and Ron, 2019). For instance, disrupted in schizophrenia 1 (DISC1) and neuregulin (NRG), which are implicated synaptic alterations and defective cytoskeleton-related organelle transport, induce eIF3-dependent SG assembly in response to environmental stressors (Ogawa et al, 2005; Kim J.A. et al, 2016).…”
Section: Dysfunctions Of Rna and Protein Processing In Als/ftd And Momentioning
confidence: 99%
“…et al, 2016). NRG2 also localizes to SGs, and depletion of NRG2 inhibits SG aggregation to promote cell survival during ER stress (Kim J.A. et al, 2016).…”
Section: Dysfunctions Of Rna and Protein Processing In Als/ftd And Momentioning
confidence: 99%
“…There are few studies that describe NRG-2, −3 and −4 and a complete analysis of their function remains a challenge. However, NRG-2 was recently reported as a component of stress granules (SG), microscopically visible aggregates of translationally stalled messenger ribonucleoprotein complexes that are formed in response to direct stress conditions [2]. Furthermore, it was shown that NRG-2, secreted from astrocytes, bound to ErbB3 on neurons and promoted neuronal survival [3].…”
Section: Introductionmentioning
confidence: 99%